Using survey data to estimate intergenerational mobility in income and education in Portugal - Clemente-Casinhas, L.; Martins, L. F.; Ferreira-Lopes, A. (Social Indicators Research, 2025)
Previous studies about intergenerational mobility for the Portuguese economy find that education and income persistence is very high in comparison with other developed economies. We construct relative, absolute, global and local measures of mobility for Portugal, comparing them with existing evidence for this and other countries. These are the intergenerational income elasticity (computed using the two-sample two-stage least squares method), income correlation, rank-rank slope, bottom to top income level probability, the share of individuals earning more than their fathers and also the intergenerational education correlation, the low to high education level probability, and the share of individuals with a higher education level than their fathers. We consider the 1968-1988 cohorts and the 1995 and 2019 waves of the European Community Household Panel and the European Union Statistics on Income and Living Conditions, respectively. Overall, based on the point estimates, women seem to present more mobility in income. Upward income mobility is verified at the bottom while persistence exists at the top. Women present a greater absolute educational mobility. More than 80% of individuals have a higher education than their fathers and full upward education mobility exists for children of low-educated fathers. Mobility in education is higher for the offspring of medium-high-income fathers. Individuals with a high education level, in the medium-high income level or with occupations requiring a higher education level show higher mobility.